AtSTP6, a new pollen-specific H+-monosaccharide symporter from Arabidopsis - Scholz-Starke, Joachim; Büttner, Michael; Sauer, Norbert (Plant physiology, 2003)
This paper describes the molecular, kinetic, and physiological characterization of AtSTP6, a new member of the Arabidopsis H+/monosaccharide transporter family. The AtSTP6 gene (At3g05960) is interrupted by two introns and encodes a protein of 507 amino acids containing 12 putative transmembrane helices. Expression in yeast (Saccharomyces cerevisiae) shows that AtSTP6 is a high-affinity (K m = 20 μm), broad-spectrum, and uncoupler-sensitive monosaccharide transporter that is targeted to the plasma membrane and that can complement a growth deficiency resulting from the disruption of most yeast hexose transporter genes. Analyses ofAtSTP6-promoter::GUS plants and in situ hybridization experiments detected AtSTP6expression only during the late stages of pollen development. A transposon-tagged Arabidopsis mutant was isolated and homozygous plants were analyzed for potential effects of the Atstp6mutation on pollen viability, pollen germination, fertilization, and seed production. However, differences between wild-type and mutant plants could not be observed.
Im Titel ist "+" hochgestellt
Gesehen am 24.08.2017